Virtual Teaching Together: engaging parents and young children in STEM activities - Zucker, Tricia A.; Mesa, Michael P.; Assel, Michael A.; McCallum, Cheryl; DeMaster, Dana (Frontiers in Psychology, 2024)
Introduction Early informal learning experiences are essential for sparking long-term interest in science, technology, engineering, and math (STEM). In a prior study, we found more promising parent involvement outcomes when families of young children were provided with STEM family education events along with home STEM activity kits compared to providing workshops alone. This study was a conceptual replication using the same program—Teaching Together STEM—to deliver educational workshops plus home activity kits; however, we varied the delivery method by using virtual “funshops” to evaluate if parents perceived this modality as feasible and useful. Methods Museum informal science educators introduced four units via virtual video chat sessions linked to 12 hands-on STEM activities that were mailed to families randomly assigned to the treatment group. Half of the families were assigned to a waitlist control group that received a portion of the virtual program after the posttest. Participants included 60 families with children aged 3 to 5 years from diverse linguistic and socioeconomic backgrounds. Results Our results indicate no significant group differences in the primary outcome of parents’ involvement in informal STEM but a small, positive effect size (ES = 0.18) that was similar in magnitude to the prior, in-person study. Although parents mostly perceived the remote delivery as convenient and the materials as engaging for their child, there were no significant program impacts on children’s general science interests (ES = −0.19). Discussion Despite the convenience, parents reported time was a barrier to doing STEM activities at home. Parents with lower education levels were less likely to attend, suggesting virtual approaches are not sufficient for ensuring broad access to family engagement programs for populations underrepresented in STEM.